2019
DOI: 10.1089/neu.2018.5869
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Surgery for Traumatic Acute Subdural Hematoma in an Aging Population

Abstract: There is uncertainty as to the optimal initial management of patients with traumatic acute subdural hematoma, leading to regional variation in surgical policy. This can be exploited to compare the effect of various management strategies and determine best practices. This article reports such a comparative effectiveness analysis of a retrospective observational cohort of traumatic acute subdural hematoma patients in two geographically distinct neurosurgical departments chosen for theirapriori defined-diverging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…IV analysis is becoming more popular in TBI research. Several recently published TBI studies analyzed effectiveness at the hospital level, 47 50 and a large European CER study is planning to use hospital-level analysis to assess effectiveness of many TBI interventions. 51 Previous studies typically divided hospitals into groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…IV analysis is becoming more popular in TBI research. Several recently published TBI studies analyzed effectiveness at the hospital level, 47 50 and a large European CER study is planning to use hospital-level analysis to assess effectiveness of many TBI interventions. 51 Previous studies typically divided hospitals into groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since the BTF guideline, which was based on merely retrospective studies with small or selected study populations that were performed more than 10 years before the guideline,5 10 11 46 there have been only some comparative studies. In our own retrospective analyses, early ASDH evacuation might be associated with lower odds of mortality and unfavourable outcome (GOS ≦3) 41. This is the first report showing an effect estimate of surgery for ASDH.…”
Section: Discussionmentioning
confidence: 68%
“…Importantly, the effect of surgery is probably not uniform, as is suggested by empirical evidence41 42 and by clinical experience. Therefore, effect modification by the following variables will be tested using interaction terms: GCS of ≥9, haematoma size >10 mm in diameter, midline shift >5 mm, time to treatment and baseline prognostic risk 30…”
Section: Methods and Designmentioning
confidence: 99%
“…Indeed, establishing causality based on non-randomized data is often impossible because of confounding by indication. A recent study comparing treatment strategy on a center level rather than on a patient level to reduce confounding by indication showed that an aggressive surgical management strategy was associated with better outcome in an elderly population with t-ASDH [ 30 ]. A systematic review regarding functional outcome of surgically and conservatively treated acute subdural hematoma patients is currently in the making [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no satisfactory conclusion regarding a preferred treatment strategy can be drawn from these studies. A recent study conducted by the authors, which compared treatment strategy on a center level rather than on a patient level to reduce confounding by indication, showed that an aggressive surgical management strategy was associated with better outcome in an elderly population with traumatic ASDHs [ 30 ]. Few studies have specified the type of intervention, and if they did, they did not address the effectiveness of the procedure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%